Axiomatizations of second price auctions with a reserve price. (22nd August 2013) - Sakai, Toyotaka
Abstract: In single‐item auctions, we show that an auction rule satisfies weak efficiency, strategy‐proofness, and non‐imposition if and only if it is either a second price auction with a reserve price or the no‐trade rule. In this characterization, any reserve price is endogenously derived from the three axioms. We also analyze relations between equity and efficiency axioms, and obtain alternative characterizations.